Seroprevalence of Paratuberculosis in Cattle and Buffaloes in various Regions of Pakistan: A Comparative Study - Khaskheli, Naheed (Revista Electronica de Veterinaria, 2023)
Paratuberculosis (PTB) is a chronic disease of cattle and other ruminants and disease. It is characterized by severe diarrhea and weight loss. The affected animals eventually die after a prolonged course. Very few studies had previously been conducted in Pakistan on the prevalence of this disease. The present was aimed at knowing the prevalence of this infection in certain important districts of Pakistan. A total of 300 milk samples were collected from apparently healthy cattle and buffaloes at livestock holdings in five districts of Pakistan i.e., Karachi (n=68), Quetta (n=51), Peshawar (n=60), Lahore (n=66) and Islamabad (n=55). The milk samples were processed for separation of lactserum and then an indirect ELISA was conducted to test for the presence of antibodies in these samples against the infection. The milk samples found to be positive were only from two districts i.e. Quetta and Karachi. The samples from rest of the districts were found to be negative. The prevalence rate in Quetta was 13.73% and 2.94% in Karachi. The combined prevalence rate of both cities was 7.56%. The statistical analysis showed that the probability of the occurrence of PTB was 5.3 times higher in the district Quetta as compared to the district Karachi (p ≤ 0.05). No association of the prevalence of the disease with any other factor i.e. animal species (cattle or buffalo), age, milk yield, and farmer education was noted. Though the present study suggests a low prevalence of the disease in the major districts of Pakistan, further studies are needed to get a clear picture of the disease in the various regions of Pakistan.